Highly time-resolved heat flux measurement in a combustion engine. (June 2023) - Huber, Konstantin; Gackstatter, Felix; Rödiger, Tim; Wensing, Michael
In this study a fast-response Atomic Layer Thermopile (ALTP) based heat flux measurement system is used for wall heat-flux determination in the combustion chamber of a commercially available SI-gasoline combustion engine. The ALTP system provides further process variables that supplement conventional cylinder pressure data with data that are highly resolved in time and location. The newly developed sensor modules were precisely calibrated and compared with other measurement techniques with radiation- and convection-based procedures. Quantitative highly time-resolved measurements with frequency resolutions up to 1 MHz are performed in the engine from low to full load and up to full speeds. Single-cycle and cycle-to-cycle measurements display the quality and high temporal resolution of the measurement system. The comparison of pressure and the heat-flux measurements shows the benefits of ALTPs for detection of engine, combustion and flow characteristics. The time progression of the heat flux curves and their autocorrelated signals show only minor noise interference. The measured results display significantly higher local peak heat flux densities with values up to 1250 Wcm −2 for certain measurement points and engine conditions than reported previously in literature for SI engines. A regression analysis suggests that the high peak heat flux densities obtained are caused by the significant higher engine power-levels per cylinder. The measured data compare well with regressions extrapolated from reported literature data. A provided uncertainty analysis revealed significant influencing parameters. The variation of thermal wall parameters with 20%–30% uncertainty are playing an essential role in particular.